Identification of Clay Mineral Content Using Spectral Gamma Ray on Y1 Well in Karawang Area, West Java, Indonesia. - Rahmat Catur Wibowo; Alia Puja Pertiwi; Suci Kurniati (Journal of Geoscience, Engineering, Environment, and Technology, 2020)
Northwest Java Basin (NWJB) is one of the proven hydrocarbon basins in Indonesia. The scope of this paper will focus onthe shales and sandstone interval within Y1 well in Karawang area, NWJB, Indonesia.A cored interval from Y1 well was chosen for an investigation of the clay minerology for the gamma-ray activity and with the purpose of determining how the Spectral Natural Gamma (SNG) log could be used as an indicator of source rock and reservoir quality. The Th/U as a redox indicator is used to assert that the shales are of anoxic conditions of shallow marine environments. Despite the relatively high insoluble Th values (60-74.15) ppm, the presence of U in substantial amounts, which only occurs in reducing conditions where it is preserved as a lower insoluble valence (U4+) explains for the low Th/U values ranging between (5.8-7.1) ppm/ppm. The overall Th/U value of the evaluated shales remain less than 25, where Th/U <25 is suggestive of marine sediments, whereas Th/U <4 is indicative of marine black shales of reducing conditions. Although no linear relationship was found between clay content and K, Th, or U, the K content characteristic three discrete reservoir characteristic (RC). The RC-I has predicted a matrix-supported texture with the highest K signal, illite and illitised kaolinite are roughly equal in importance as source of K. The RC-II has predicted a grain-supported texture with intermediate K content. K-feldspar, mica and illite as the main sources. The RC-III has predicted have a low K content with grain-supported texture and most of the K is hosted in feldspar. Overall, the laboratory measurements appear to be applicable to the log data, and, using SEM or XRD, the detail facies subdivision can be extended throughout the source rock and reservoir section based on the SNG log.